Tectonic Evolution of the Intra-plate Structures of Sarmatia in the Phanerozoic. 1. Geophysical analysis of structural and substance differentiation of the lithosphere and tectonic divisibility of the Earth’s crust - Bartaschuk, Oleksii; Suyarko , Vasyl; Chuienko , Oleksandr; Perry , Bruce J. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Purpose. The structure of the Sarmatia`s llithospheric plate was studied based on the latest integrated geological, geophysical, tectonophysics, aerocosmo-geological, neo-tectonic data and the gravity, magnetic, dense and seismic (GSZ, seismotomography) modeling data. The aim of the study to reveal the nature of heterogeneities of the Sarmatia Lithosphere and their influence on the nature of the process of structural and material differentiation of the Earth’s continental crust. Method. A comparative geotectonic analysis of the structure, composition, and relationships of individual layers of the consolidated crust, the Moho section, and the sub-crustal mantle was performed. According to the results of the analysis, the nature of the relationship between the structure and composition of the Lithosphere component surfaces and the layers of the Earth’s crust, the peculiarities of the tectonic division of the Pre-Rifean craton core of Sarmatia were clarified. Results. The relationship and regularities of the spatial distribution of individual floors of the Lithosphere, the layers of the Earth’s continental crust and the core-mantle mixture, the structure of the Moho interface and the sub-crustal mantle on the territory of Ukraine have been clarified. Based on the comparison of the modern segmentation of the consolidated crust with the structure of the lithosphere layers, it was established that the modern structural and material heterogeneity of the Sarmatia plate core is determined by the original, "built-in" anisotropy of the Lithosphere, while the structure of the Earth’s crust does not have an unequivocal connection with the relief of the sole of the modern seismic lithosphere. Exceptions are its rise with the formation of mantle dome structures in separate areas of the Western and Eastern micro-plates and under the Lokhvytskyi segment of the Dnipro-Donetsk Avlacogen. Scientific novelty. The nature of the impact of the heterogeneity of the Sarmatia`s lithosphere, "frozen" during the stabilization of the Pre-Rifean craton core of the East European Platform, on the modern segmentation and structural-material differentiation of the Earth’s continental crust has been clarified. Scientific novelty. For the first time, a conclusion was made about the deformational nature of the structural differentiation of the continental crust of Sarmatia, which was formed against the background of the initial anisotropy of the Lithosphere under the influence of processes of mantle activation at the stages of tectonic evolution in the Phanerozoic. Practical significance. The obtained data on the geodynamic relationship between the structural surfaces of the lithosphere, the layers of the Earth’s crust and the coromantium mixture can be used for geological interpretation when elucidating the geodynamic conditions of the formation and tectonic evolution of the intra-plate geostructures of Sarmatia in the Phanerozoic.